2022
DOI: 10.30601/dedikasi.v6i2.3072
|View full text |Cite
|
Sign up to set email alerts
|

Learning L3 English Early: A Danger to L1 Indonesian Language Acquisition?

Abstract: Since the future of the world is English, many countries now include English in their primary education curriculum, so language proficiency can be achieved more quickly and effectively. As two or more languages knowledge are competing linguistically in the brain, the early introduction to English means putting the other languages known by the Indonesian English language learners in a competition. On the other hand, despite its controversy, bilingualism and multilingualism, when achieved fully and proportionall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…The study also revealed that learning facilities have a positive impact on students' language learning achievement because it affects the learners' motivation to learn a language. This finding is also relevant to what is mentioned in the Background Section, that most students are unprepared to express themselves in a foreign language daily (Irnanda, 2021) and they express it by pointing out the facility problem as the root problem. Students in MIA are not allowed phones and also do not have a multimedia room that can support more interactive and fun learning.…”
Section: Figure 1 the Facility Factorsupporting
confidence: 55%
See 2 more Smart Citations
“…The study also revealed that learning facilities have a positive impact on students' language learning achievement because it affects the learners' motivation to learn a language. This finding is also relevant to what is mentioned in the Background Section, that most students are unprepared to express themselves in a foreign language daily (Irnanda, 2021) and they express it by pointing out the facility problem as the root problem. Students in MIA are not allowed phones and also do not have a multimedia room that can support more interactive and fun learning.…”
Section: Figure 1 the Facility Factorsupporting
confidence: 55%
“…There has been controversy surrounding a particular regulation due to the fact that the languages being enforced are not familiar to the majority of the students. Specifically, English is a foreign language that is widely considered difficult to master by Indonesian-speaking learners (Lamb, 2007a;Lamb 2007b;Irnanda & Sarair, 2022). Many boarding schools disregard the fact that the students come from a zero-English environment and mostly are graduates of public primary schools that do not provide basic English lessons.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation